Кримські міста: особливості становлення, якісні та кількісні зміни наприкінці XVIII – XIX ст. - Анісімова, О.С. (Культура народов Причерноморья, 2013)
У статті розглядаються особливості якісних і кількісних змін у структурі кримських міст. Досліджено, в яких історичних умовах здійснювався їх розвиток. Розглянуто типи міст, які існували на півострові наприкінці XVIII – XIX ст. Введено в науковий обіг архівні відомості, що проливають світло на особливості адміністративних перетворень міст. В статье рассматриваются особенности качественных и количественных изменений в структуре крымских городов. Исследовано, в каких исторических условиях осуществлялось их развитие. Рассмотрены типы городов, которые существовали на полуострове в конце XVIII – XIX вв. Введены в научный оборот архивные сведения, проливающие свет на особенности административных преобразований городов. Highlights of development of the cities of the Crimea after their accession in structure of the Russian Empire are considered. Process of transformation of existing settlements in such which would answer new standards of the Russian cities is tracked. Besides, circumstances of establishment of new settlements which appeared as a result of activity of the imperial power are investigated. Historical conditions against which administrative transformation of the cities was carried out are studied. Features and specifics in development of the cities of the Crimea are revealed. Besides, dynamics of changes of their qualitative and quantitative structure is tracked. As shown in article, administrative changes in the Crimea became an important starting point in development of the Crimean cities. It is investigated that represented settlements which according to the Russian legislation became the cities. Local features against which administrative transformations were carried out are revealed. The overall picture illustrating dynamics of receiving and changes of the statuses of the Crimean cities is recreated. It is shown that this process, in turn, was closely connected with a level of development of municipalities of the respective cities. It is visually shown that the level of development of the cities as a whole can conditionally be accepted as productivity of activity of municipalities. And their success, in turn, depended on the administrative status of the city.